Optimization on Supercritical CO2 Extraction Process to Improve the Quality of Patchouli Oil by Response Surface Methodology Approach - Edi Priyo Utomo; Marina Marina; Warsito Warsito; Egi Agustian (Universitas Gadjah Mada, 2018)
Until now, the patchouli oil is the largest commodity export of essential oil for Indonesia. But the price of patchouli oil is often unstable due to the quality of oil which fluctuates depending on the components. To improve the performance and quality of patchouli oil had been carried out the purification process using supercritical CO2 fluid extraction method. Optimization conditions of the extraction process using the approach of Response Surface Methodology (RSM) and the influence of independent variables include temperature (35–45 °C), pressure (80–150 atm) and the time of extraction (60–300 min), and then evaluated using a Box-Behnken Design (BBD). Analysis of the components in the extract was carried out by using GC-MS and GC-FID to detect the changes of compositions of the components containing the oil before and after the extraction process. The optimum condition of supercritical extraction within experimental range of the studied variables was at 38 °C, 146.35 atm and 74 min for predicted oil yield of 6.41% and at 41.45 °C, 135.17 atm and 252.62 min and the predicted patchouli alcohol content was 25.34%. The extracted oil is enriched with the main components such as patchouli alcohol compared to the original patchouli oil. The results of RSM evaluation showed consistency between the variables contained in the experiment and the prediction.